Antiviral effects of micafungin against pteropine orthoreovirus, an emerging zoonotic virus carried by bats - Hondo, Eiichi; Katta, Tetsufumi; Sato, Ayato; Kadofusa, Naoya; Ishibashi, Tomoki; Shimoda, Hiroshi; Katoh, Hirokazu; Iida, Atsuo (Virus Research, 2024)
•A library of 2943 FDA-approved drugs was screened to find potential antiviral drugs of pteropine orthoreovirus.•Six hit compounds dramatically inhibited viral replication in vitro.•Micafungin possessed antiviral activity to multiple strains of PRV.•Micafungin suppressed PRV release in human cells. Bat-borne emerging zoonotic viruses cause major outbreaks, such as the Ebola virus, Nipah virus, and/or beta coronavirus. Pteropine orthoreovirus (PRV), whose spillover event occurred from fruits bats to humans, causes respiratory syndrome in humans widely in South East Asia. Repurposing approved drugs against PRV is an effective tool to confront future PRV pandemics. We screened 2,943 compounds in an FDA-approved drug library and identified eight hit compounds that reduce viral cytopathic effects on cultured Vero cells. Real-time quantitative PCR analysis revealed that six of eight hit compounds significantly inhibited PRV replication. Among them, micafungin used clinically as an antifungal drug, displayed a prominent antiviral effect on PRV. Secondly, the antiviral effects of micafungin on PRV infected human cell lines (HEK293T and A549), and their transcriptome changes by PRV infection were investigated, compared to four different bat-derived cell lines (FBKT1 (Ryukyu flying fox), DEMKT1 (Leschenault's rousette), BKT1 (Greater horseshoe bat), YUBFKT1 (Eastern bent-wing bats)). In two human cell lines, unlike bat cells that induce an IFN-γ response pathway, an endoplasmic reticulum stress response pathway was commonly activated. Additionally, micafungin inhibits viral release rather than suppressing PRV genome replication in human cells, although it was disturbed in Vero cells. The target of micafungin's action may vary depending on the animal species, but it must be useful for human purposes as a first choice of medical care.